Fazer estado, produzir ordem: sobre projetos e práticas na gestão do conflito urbano em favelas cariocas - Motta, Luana Dias (Universidade Federal de São Carlos, 2017)
This thesis deals with the urban conflict in contemporary Brazil, which in recent decades has had violence as the core of its figuration. Specifically, it reflects on the contours assumed by state management in the effort to contain this conflict through social projects and programs with poor populations. Looking at state management through social projects contributes to the debate about state interventions in poverty areas by highlighting other forms of intervention besides the police action, but above all by pointing out the relationship and complementarity between management via social and that one supported by state repression. The research was developed from ethnographic work carried out in the favela Cidade De Deus (City of God), in Rio de Janeiro, focused on the routine of police-teachers assigned from the local UPP to teach courses and on the work of counselors and tutors who performed individual assistance for young people. The perceptions of these state agents about the urban conflict and about the strategies to intervene with it are synthesized from the descriptions of their daily practices with the so-called vulnerable young people. Their strategies for approaching these young people, categorizing them as dangerous or virtuous, and explaining the reasons for the different profiles signal a way of doing management that is not restricted to the Cidade de Deus. There are four dimensions of this way of doing social management to be remarked. The social origin of these state agents "on the edge" is very similar to those they deal with; when "poor people are taking care of poor people" identifications and familiarity are produced, but also hierarchies and distinctions, which allow the affections and engagements to combine with the effort to produce order and normalization. The second dimension refers to the centrality of the category of vulnerable youth, not only as a part of the population but, above all, as an operating category that integrates the grid from which the urban conflict itself is read. Making vulnerable youth legible to intervene on it is an imperative. The third dimension touches on the fact that vulnerability is the metric through which it has been possible to differentiate the poor, classifying them according to the risks of them becoming agents of violence and threat to society. The fourth dimension concerns the fact that the management of urban conflict via social does not appear as an alternative to or opposes to public security; rather the social has been constituted as a complementary form of doing public security, having its objectives strongly coupled with efforts to produce order, prevent and combat violence. In this perspective, state practices directed to poor populations are increasingly synonymous with containment of urban conflict. In this sense, observing the practices of state agents who are "on the edge" of social interventions in poverty territories allows us to reveal the "making state" in and by the efforts to produce order.
Faire l’état, produir ordre: sur des projets et des pratiques dans la gestion du conflit urbain dans les favelas à Rio de Janeiro
Keywords: Conflito urbano; Práticas estatais; Legibilidades; Vulnerabilidade; Gestão da pobreza; Urban conflict; State practices; Legibilities; Vulnerability; Poverty management; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA